2015
DOI: 10.25070/rea.v7i1.142
|View full text |Cite
|
Sign up to set email alerts
|

Viabilidade Da Introdução Do Mel Na Merenda Escolar: Oportunidade E Desafio Para O Agronegócio Apícola1

Abstract: Tendo como pano de fundo a desestabilização do mercado apícola, decorrentedo bloqueio europeu às exportações brasileiras de mel, e a crescente necessidade depromover esse importante produto do agronegócio brasileiro, foi realizado este estudo,que busca avaliar a viabilidade da introdução do mel na merenda escolar, comooportunidade mercadológica dentro da abordagem teórica de Sistema AgroalimentarLocal (SIAL). Avaliaram-se a aceitabilidade e o custo de aquisição do mel, comparadosa outros dois equivalentes já u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…The objective of the research by Magalhães et al (2009) was to evaluate the feasibility of introducing honey in school meals, as a marketing opportunity within the theoretical approach of the Local Agrifood System (SIAL). It was concluded that the work related to food education and promotion of the honey product with society, in order to increase its acceptability, in addition to a policy of differentiated prices for school lunches and a logistics for the supply of the product, constitutes challenges for beekeeping agribusiness.…”
Section: Empirical Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…The objective of the research by Magalhães et al (2009) was to evaluate the feasibility of introducing honey in school meals, as a marketing opportunity within the theoretical approach of the Local Agrifood System (SIAL). It was concluded that the work related to food education and promotion of the honey product with society, in order to increase its acceptability, in addition to a policy of differentiated prices for school lunches and a logistics for the supply of the product, constitutes challenges for beekeeping agribusiness.…”
Section: Empirical Evidencementioning
confidence: 99%
“…The growth of family farming is a positive example of government incentives, strengthened in the 1990s, when the National Program for the Strengthening of Family Agriculture -PRONAF was created and later with the enactment of Law no. 11,326 of July 24, 2006. More recently, empirical studies have been developed to analyze the positive impacts on the inclusion of honey in school meals in Brazilian municipalities (Erhardt, 2008;Magalhães et al, 2009;Formiga, 2014;Staron et al, 2015;Silva, 2018;Gomes et al, 2020;Moreira et al, 2021). Most of these studies found evidence on the positive impacts of the inclusion of honey in school meals in the municipalities studied.…”
Section: Introductionmentioning
confidence: 99%
“…Historicamente, a governança no Estado brasileiro é representada pela limitação da capacidade de formular/implementar políticas públicas em função da rigidez e ineficiência do aparelho burocrático do Estado. Em trabalhos de autores como Araújo (2002), Bresser Pereira (1996, 2005a, Marini (2003), Mais recentemente, estudos empíricos foram desenvolvidos para analisar os impactos positivos sobre a inserção do mel na merenda escolar dos municípios brasileiros (Erhardt, 2008;Magalhães et al, 2009;Formiga, 2014;Staron et al, 2015;Silva, 2018;Gomes et al, 2020;Moreira et al, 2021). Grande parte desses estudos encontrou evidências sobre os impactos positivos da inserção do mel na merenda escolar nos municípios estudados.…”
Section: Introductionunclassified